Adverse reactions following COVID-19 immunization in children of elementary school age - Yusuf, Yenni; Junaedi, Ari Andini; Mutmainnah; Fadhilah, Nur Azizah; Wahyuni, Sitti (Universitas Gadjah Mada, 2024)
Purpose: Due to the low rate of parent acceptance of vaccines, this study was conducted to evaluate post-vaccination adverse events among elementary school students. Methods: This survey took place in the Manggala Subdistrict of Makassar City. The study was conducted from September to October 2022 by distributing a paper-based questionnaire regarding the COVID-19 vaccines. Results: Of 129 respondents, the age range was 7-12 years. Sixty-five percent of respondents received the first vaccine shot in January or February, with a 4-week interval of the second dose among 46.5% of children. The vaccine administered was CoronaVac from Sinovac. The most common adverse events were injection pain (45-48%) and fever (15-17%). The other side effects were itching, swelling, fever, and shortness of breath. Around 17-18 % of respondents did not have any adverse reactions. There is no increase in the risk for younger children (years 1-3) compared with older children (years 4-6). Conclusion: The children reported only mild adverse events such as injection pain, weakness, and fever. The CoronaVac has minimal side effects among elementary school children.